Estrategias para fomentar el eco-turismo en la reserva marina Isla Santa Clara - Basantes Sánchez, Cristhian Alfredo (My University, 2020)
Tourism in the Marine Reserve is very scarce throughout the year. This case study presents an on-site investigation which allows us to propose an eco-tourism development in the Santa Clara Island Marine Reserve because there is no tourism because it is a natural area protected by the National System of Protected Areas of Ecuador, this work It is seen in promoting an eco-tourism package promoting sustainable tourism where tourists can perform different activities around the Santa Clara Island in the different zoning areas, without compromising the life of the species on that Island as whale watching in the area of multiple use, and sighting of birds, sea lions, snorkeling in the area of public use, tourism and recreation and for sport fishing in the area of multiple use. In addition, it is directed with a qualitative and quantitative approach with tools such as observation, interview, travel cost and strategies to promote this eco-tourism package, also in analysis the special regulation of tourism in protected natural areas, knowing that knowing that Law information you can enjoy adventure tourism. The marine reserve is a paradise within the Province of El Oro, rich in birdlife and flora, you can identify the problems that occur on the island as well as give an improvement solution and its factors that prevent the entry of tourists, the island is disappearing in the future due to the erosion of the area, winds and rainfall
El turismo en la Reserva Marina es muy escaso en todo el año. Este estudio de caso se presenta una investigación in situ lo cual permite proponer un desarrollo eco-turístico en la Reserva Marina Isla Santa Clara debido que no hay turismo porque es un área natural protegida por el Sistema Nacional de Áreas Protegidas del Ecuador, este trabajo se ve en promocionar un paquete eco-turístico promoviendo un turismo sostenible donde los turistas puedan realizar diferentes actividades alrededor de la Isla Santa Clara en las diferentes zona de zonificación, sin comprometer la vida de las especies en dicha Isla como avistamiento de ballenas en la zona de uso múltiple, y avistamiento de aves, leones marinos, snorkel en la zona de uso público, turismo y recreación y para la pesca deportiva en la zona de uso múltiple. Además, va dirigido con un enfoque cualitativo y cuantitativo con herramienta como la observación, entrevista, costo de viaje y estrategias de como impulsar este paquete eco-turístico, también en analizar el reglamento especial de turismo en áreas naturales protegidas, sabiendo que con conocer dicha ley se podrá gozar del turismo de aventura. La reserva marina es un paraíso dentro de la Provincia de El Oro, rica en avifauna como en flora, se logró identificar los problemas que se da en la isla así mismo dar una solución mejora y sus factores que se impide el ingreso de turistas, la isla esta en desaparecer en el futuro debido a la erosión del área, vientos y precipitaciones
Keywords: ISLA; RESERVA MARINA; TURISMO SOSTENIBLE